Performance Ranking of Arterial Corridors Using Travel Time and Travel Time Reliability Metrics. Issue 1 (January 2015) - Day, Christopher M.; Remias, Stephen M.; Li, Howell; Mekker, Michelle M.; McNamara, Margaret L.; Cox, Edward D.; Bullock, Darcy M.
Performance measures are essential for managing transportation systems and demonstrating agency accountability. Probe vehicles are an effective means for gathering vast amounts of information about highway networks. This paper presents a scalable methodology for analyzing arterial travel times that considers both the central tendency and the reliability of the travel time. A pilot analysis was carried out for 28 arterials with a total of 341 signalized intersections across Indiana. Starting from individual minute-by-minute speed records, the data were converted into travel times and aggregated into time series cohorts that correspond to typical traffic signal time-of-day periods. The data were normalized for the ideal travel time (based on the speed limits on each route) to account for individual route lengths and speeds. The data were compiled for all Wednesdays from January through July 2014 for investigation of arterial characteristics. The results show that a greater density of traffic signals on a route loosely corresponds to higher average travel times and less reliability. A composite index incorporating both the average values and reliability characteristics of travel time is developed and is used to rank the arterials by performance.